2014
DOI: 10.1517/14740338.2014.937422
|View full text |Cite
|
Sign up to set email alerts
|

Statin myopathy: the fly in the ointment for the prevention of cardiovascular disease in the 21st century?

Abstract: Knowledge gaps in the field of statin myopathy are identified and future research directions are suggested. We urge the need for international attention to address this important, but largely neglected clinical problem, that if unresolved will remain an impediment to the effective prevention and treatment of CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 71 publications
0
33
0
Order By: Relevance
“…Despite treatment of these, a residual risk remains. Other barriers include nonadherence with statin therapy, often due to adverse effects [8,9], particularly myopathy; genetic disorders such as familial hypercholesterolemia (FH) causing extremely high plasma levels of LDL-C that cannot be sufficiently lowered by statin therapy alone [10]; and elevation in the plasma concentration of lipoprotein(a) [Lp(a)], an atherogenic LDL-like particle for which no proven therapeutic agent exists [11]. Late detection and treatment of atherogenic dyslipidemia also presents a challenge to cardiovascular risk reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Despite treatment of these, a residual risk remains. Other barriers include nonadherence with statin therapy, often due to adverse effects [8,9], particularly myopathy; genetic disorders such as familial hypercholesterolemia (FH) causing extremely high plasma levels of LDL-C that cannot be sufficiently lowered by statin therapy alone [10]; and elevation in the plasma concentration of lipoprotein(a) [Lp(a)], an atherogenic LDL-like particle for which no proven therapeutic agent exists [11]. Late detection and treatment of atherogenic dyslipidemia also presents a challenge to cardiovascular risk reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Despite best efforts, including modified dosing strategies and specialist input, ~30% of these patients will not be able to take a statin . Myopathy, gastrointestinal symptoms and elevated liver enzymes account for most cases of statin intolerance …”
Section: Need For New Therapies Targeting Apob100‐containing Lipoprotmentioning
confidence: 99%
“…48 Myopathy, gastrointestinal symptoms and elevated liver enzymes account for most cases of statin intolerance. [49][50][51] Statin-associated muscle symptoms (SAMS) include any muscle pain or weakness, with or without elevated plasma levels of creatine kinase, and incorporate myalgia, myositis, rhabdomyolysis and asymptomatic elevations in creatine kinase. 52 It is noteworthy that myopathy was reported in many statin trials as being no more frequent in statin-treated groups than placebo groups.…”
Section: Statin Intolerancementioning
confidence: 99%
“…Nonetheless, in Germany, there is a lack of reliable data, such as how frequently muscle disorders and muscle ailments occur. The frequency estimates of statin intolerance are scattered in the literature depending on the definition and investigation method, from 0.01% to 10% . Registries and observational studies identified values from 7% to 29% .…”
Section: Introductionmentioning
confidence: 99%
“…The frequency estimates of statin intolerance are scattered in the literature depending on the definition and investigation method, from 0.01% to 10%. 13 Registries and observational studies identified values from 7% to 29%. 14,15 In clinical trials (RCTs), in contrast, there are only minor differences in the side effects compared to placebo.…”
mentioning
confidence: 99%